Caracterização da estrutura sub-superficial da ilha do Faial (Açores) - Neves, Samuel (2014)
The aim of this communication is to present the velocity models of propagation of seismic waves P and S using geophysical methods, such as refraction surveys, MASW (Multichannel Analysis of Surface Waves), and Horizontal-to-Vertical spectral ratio ambient-noise in Faial Island (Azores). After determining the velocity models and ratios H/V, the results were compared for the same location, with previous works of ambient-noise and with lithology of the island. These results providing important physical parameters for a near surface characterization of the soil structure and to predict seismic ground motion in this region.